Brazilian Guitar Music: identidade e estereótipo no repertório brasileiro para violão solo - Marco Ernesto Teruel Castellon (2017)
The purpose of this document is to discuss the interactions between national identity and stereotype within the Brazilian classical guitar (Violão) repertoire and display the variety of styles and genres that are performed in the instrument. To do so I focused on the works of performer-composers born after 1950. Departing from the assumption that the Violão was transformed into a symbol of brazilianness for being strongly associated to specific genres of Brazilian music, and the result ofthis strong association was that the label Brazilian guitar was boundto imply a determinate type of music that is dominant in Brazil and is related to the invention of Brazilian tradition. This fact creates a distortion that leads other types of music to the margin of the debates of Brazilian music and finally gives a distorted and biased view of what the musical production for solo guitar in Brazil. With an interdisciplinary approach enlisting historical and sociological concepts, the present work aims to point new and more pertinent options to understand the Brazilian contemporary repertoire.